2010
DOI: 10.1007/s10560-010-0204-y
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Adolescent American Indians: Preventative Social Work Programs

Abstract: Suicide is a leading social problem among the adolescent American Indian community. This literature review examines the demographics of American Indian adolescents who attempt suicide, along with the effects it has on the entire family/community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…There is a growing body of literature about culturally relevant suicide preventive interventions for Native American communities (Hamilton & Rolf, 2010;Middlebrook et al, 2001). LaFromboise and colleagues (LaFromboise & Howard-Pitney, 1995;LaFromboise & Lewis, 2008) developed the Zuni Life Skills Development Program, a suicide preventive intervention that focused on life skills training for high school students in a New Mexico Zuni reservation.…”
Section: Principle 6: Adopt Culturally Relevant Suicide Preventive Inmentioning
confidence: 99%
“…There is a growing body of literature about culturally relevant suicide preventive interventions for Native American communities (Hamilton & Rolf, 2010;Middlebrook et al, 2001). LaFromboise and colleagues (LaFromboise & Howard-Pitney, 1995;LaFromboise & Lewis, 2008) developed the Zuni Life Skills Development Program, a suicide preventive intervention that focused on life skills training for high school students in a New Mexico Zuni reservation.…”
Section: Principle 6: Adopt Culturally Relevant Suicide Preventive Inmentioning
confidence: 99%
“…A review of studies evaluating outcomes of mental health care found no such studies for AI populations (Miranda et al, 2005), raising the question of whether it is appropriate to promote the use of such evidence-based treatments in these populations. Efforts to reduce behavioral health disparities experienced by AI/AN children and adolescents have focused on substance abuse or suicide prevention interventions that build upon traditional AI cultural strengths (Hamilton & Rolf, 2010;LaFromboise & Lewis, 2008;Moran & Bussey, 2007;Muehlenkamp, Marrone, Gray, & Brown, 2009) or adapting and implementing western evidence-based interventions (Dionne, Davis, Sheeber, & Madrigal, 2009;Goodkind, LaNoue, et al, 2010;Morsette et al, 2009).…”
mentioning
confidence: 99%
“…Such positive familial environments mediate the negative impact of suicide attempts, and opioid misuse [ 33 , 51 ]. Schools could also play a critical role in mitigating the risk for suicide attempts and opioid misuse by establishing teen health centers in schools with an on-site mental health counselor, and incorporating behavioral health skills development into the curricula [ 5 ], such as teaching students first aid skills for suicide prevention through role-play and group discussions [ 61 ]. At the community level, AI/AN elders could collaborate with schools to visit classrooms and help youth connect with their culture, traditions and heritage through elder taught lessons [ 62 ], and also connect students to tribal ceremonies [ 63 ].…”
Section: Discussionmentioning
confidence: 99%